Association Between Foot Surgery Type and Subsequent Healing in Veterans With Moderate-to-Severe Diabetic Foot Infections. (24th December 2021) - Kim, Justin J; Littman, Alyson J; Sorkin, John D; Roghmann, Mary-Claire
Abstract: Background: Diabetic foot infections are a common precursor to lower extremity amputations. The treatment of diabetic foot infections involves both medical and surgical management, of which limb-sparing surgeries are increasingly preferred over amputations at or above the ankle to preserve mobility and quality of life. The outcomes following these limb-sparing surgeries are not well described. Methods: This was a single-center, retrospective cohort study of 90 Veterans with moderate-to-severe diabetic foot infections between 2017 and 2019 from the Veterans Affairs Maryland Health Care System. The exposure was foot surgery with bone resection (ie, toe amputation, metatarsal resection, transmetatarsal amputation) vs debridement alone. The outcome was healing within 1 year. We used log-binomial regression to assess the association between foot surgery type and healing, stratify by infection location, and evaluate potential confounding variables. Results: The cumulative incidence of healing after foot surgery with bone resection was greater than that following debridement (risk ratio [RR], 1.80 [95% confidence interval CI, 1.17–2.77]). This association was modified by infection location and greater for toe infections (RR, 4.52 [95% CI, 1.30–15.7]) than other foot infections (RR, 1.19 [95% CI, .69–2.02]). We found no evidence of confounding by comorbidities or infection severity. Conclusions: For patients with toe infections, foot surgery with bone resection was associated with better healing than debridement alone. The multiple specialties caring for patients with diabetic foot infections need a stronger common knowledge base—from studies like this and future studies—to better counsel patients about their treatment and prognosis. Abstract : For moderate-to-severe diabetic foot infections of the toe, we found that foot surgery with bone resection was associated with better healing than debridement. For infections of other parts of the foot, healing was similar between bone resection and debridement.